"Did that play of mine …?": James Connolly, Cathleen Ni Houlihan and staging revolution. Issue 4 (1st October 2016) - Lusk, Kirsty
Abstract: Despite the crucial position he occupies in Irish history as one of the leaders of the Easter Rising, and the political – and emotional – impact of his subsequent execution, while wounded, by the British Army on 12 May 1916, the writings of Edinburgh-born James Connolly have often been overlooked in both Irish and Scottish studies, and not just in accounts of the Rising but also in the wider context of cultural connections, including cultures of commemoration. In particular, Connolly's surviving literary work, including Under Which Flag ?, the drama staged on the eve of Easter 1916, as well as poems and songs, has had limited attention. This article reconsiders Under Which Flag? in comparison with Yeats and Gregory's Cathleen ni Houlihan in order to demonstrate the central place the drama holds as a continuation – and complication – of Connolly's political and journalistic writings. If Connolly is a neglected figure as a writer – as opposed to a political leader and martyr – then the play he left behind (once thought to have been lost, like another of his dramas, The Agitator's Wife ) affords us an opportunity to reassess his contribution to the struggle for independence as part of its literary wing.